1989
DOI: 10.1248/bpb1978.12.37
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitions of metabolic responses of polymorphonuclear leukocytes by antiallergic drugs.

Abstract: Sites of the inhibitory actions of antiallergic and antihistaminic drugs on polymorphonuclear leukocytes were examined by means of measurements of arachidonic acid release, superoxide anion generation and changes in membrane potential. The results obtained in this study were as follows. (i) Azelastine, an antiallergic drug, inhibited arachidonic acid release as well as superoxide generation. However, high concentrations of azelastine diminished the charge of the cells. (ii) Clemastine, used as an antihistamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…On the other hand, the acidic agents were developed on the basis of ob servations that DSCG (disodium cromogly cate), bicalein and caffeic acid are inhibitors of chemical mediator release (12,15). We have previously shown that superoxide generation, arachidonic acid release as well as changes of membrane potential were sup pressed by one of the basic antiallergic agents, azelastine (16)(17)(18). In this study, we attemped to compare the inhibitory effects of antial lergic drugs on the release of arachidonic acid, leukotriene B4 and superoxide from ac tivated human neutrophils to clarify the action sites of the various basic and acidic anti allergic drugs.…”
mentioning
confidence: 99%
“…On the other hand, the acidic agents were developed on the basis of ob servations that DSCG (disodium cromogly cate), bicalein and caffeic acid are inhibitors of chemical mediator release (12,15). We have previously shown that superoxide generation, arachidonic acid release as well as changes of membrane potential were sup pressed by one of the basic antiallergic agents, azelastine (16)(17)(18). In this study, we attemped to compare the inhibitory effects of antial lergic drugs on the release of arachidonic acid, leukotriene B4 and superoxide from ac tivated human neutrophils to clarify the action sites of the various basic and acidic anti allergic drugs.…”
mentioning
confidence: 99%
“…Moreover, ketotifen may act on inflammatory cells other than mast cells. For example, it may reduce the functions of mobility and phagocytosis of polymorphonuclear cells [43], it may reduce the chemotaxis of neutrophils [44] or it may inhibit their metabolic responses [45]. It also inhibits leukotriene C 4 release and PAF-induced chemotaxis of eosinophils [46].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that it prevents the synthesis/release of mediators such as histamine (Chand et al, 1985), leukotrienes (Chand et al, 1989;Nishihira et al, 1989), superoxide anions (Busse et al, 1989;Taniguchi & Takanaka, 1989), arachidonic acid (Taniguchi & Takanaka, 1989), and that it antagonizes the effect of some of these mediators on target organs (Rafferty et al, 1989). In addition, Nakamura et al (1988) have shown that azelastine inhibits the release of Ca2+ from intracellular storage sites in guinea-pig peritoneal macrophages stimulated by PAF or by FMLP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Nakamura et al (1988) have shown that azelastine inhibits the release of Ca2+ from intracellular storage sites in guinea-pig peritoneal macrophages stimulated by PAF or by FMLP. Azelastine was also described as an inhibitor of leukocyte (Chand et al, 1985;Taniguchi & Takanaka, 1989;Busse et al, 1989), and platelet functions (Achterrath-Tuckermann et al, 1988). Azelastine is effective in animals (Chand et al, 1986;AchterrathTuckermann et al, 1988), and has been claimed to reduce allergic rhinitis (Meltzer et al, 1988) and asthma Kemp et al, 1987).…”
Section: Discussionmentioning
confidence: 99%